1-Sulfonyl-6-Piperazinyl-7-Azaindoles as potent and pseudo-selective 5-HT6 receptor antagonists. Issue 11 (1st June 2016) - Fabritius, Charles-Henry; Pesonen, Ullamari; Messinger, Josef; Horvath, Raymond; Salo, Harri; Gałęzowski, Michał; Galek, Mariusz; Stefańska, Klaudia; Szeremeta-Spisak, Joanna; Olszak-Płachta, Marta; Buda, Anna; Adamczyk, Justyna; et al.
Graphical abstract: Abstract: A series of 1-Sulfonyl-6-Piperazinyl-7-Azaindoles, showing strong antagonistic activity to 5-HT6 receptor (5-HT6 R) was synthesized and characterized. The series was optimized to reduce activity on D2 receptor. Based on the selectivity against this off-target and the analysis of the ADME-tox profile, compound1c was selected for in vivo efficacy assessment, which demonstrated procognitive effects as shown in reversal of scopolamine induced amnesia in an elevated plus maze test in mice. Compound3, the demethylated version of compound1c, was profiled against a panel of 106 receptors, channels and transporters, indicating only D3 receptor as a major off-target. Compound3 has been selected for this study over compound1c because of the higher 5-HT6 R/D2 R binding ratio. These results have defined a new direction for the design of our pseudo-selective 5-HT6 R antagonists.